The Use of Bilingual Flashcards as Learning Media to Teach English Vocabulary for Young Learners - Darsana, Kadek Indira Putri Dewi (STKIP AGAMA HINDU SINGARAJA, 2025)
This study aims to analyze the implementation of bilingual flashcards as a learning medium in teaching English vocabulary to kindergarten students at A Public School in Singaraja and explore teachers' opinions regarding its use. This study used a qualitative descriptive method involving three teachers as research subjects. Data were collected through participant observation, in-depth interviews, and open-ended questionnaires. The results showed that bilingual flashcards were implemented in the main activity during circle time, with each teacher having a different role. The learning strategies used were game-based, such as Show and Tell, Find the Flashcard, Match the Animal, and Role Play. In the pre-activity stage, teachers focused on creating a comfortable learning environment so that students were ready to receive the material. While in the post-activity stage, flashcards were used to review vocabulary through discussion, repetition games, and pronunciation exercises. Teachers also implemented formative assessment by observing students' understanding through verbal interaction and activity participation. Besides that, the three teachers argued that bilingual flashcards were an effective learning medium for teaching English vocabulary. This media helps to increase students' motivation, facilitates memorization and recall of vocabulary, improves vocabulary mastery, and makes learning more fun and interactive. However, this study also found several challenges, such as inadequate card size, the potential for increased noise in the classroom, demands for more creativity for teachers, less effectiveness for non-visual students, and the tendency for students to become dependent on flashcards.